The experience of culture through a Singaporean chinese diaspora. - Guo, Yixiu. (2012)
Inspired by a sense of displacement, the artist embarked on a research project, attempting to ask if there was a universal Singaporean culture that was beyond the multicultural condition Singapore posits itself in. The two primary subject matters explored are the tissue paper culture in Singapore; where one uses a tissue paper packet to "Chope" (reserve) seats, as well as the Hawker Centre as a social space. Through a combination of theoretical thinking and personal reflections through art, the artist presents her findings and conclusions.